Thermodynamics of Synthesis of New Phenoxazine Derivatives - V. José Cotuá; Sandra Cotes; Fernando Castro; Pedro Castro (Journal of Basic & Applied Sciences, 2013)
This article describes a semi-empirical study on the thermodynamics involved in the synthesis of three novel ortho, meta and para, potentially intercalatingphenoxazine 1 derivatives o-(6), m-(7) and p-(8). Quantum chemical calculations at the semi-empirical PM3 method were used in order to evaluate conformational states of the molecules, as well as to predict thermodynamic properties and equilibrium constants. The more favourable product was found to be the compound with the methoxy group in ortho-position. The methoxy group in para-position hinders the reaction by steric factor, which is reflected from the small constant, Kp.